Retrospective US database analysis of drug utilization patterns, health care resource use, and costs associated with adjuvant interferon alfa-2b therapy for treatment of malignant melanoma following surgery - Krishna A; Hackshaw MD; Mauro DJ (Dove Medical Press, 2012)
Michelle D Hackshaw,1 Arun Krishna,2 David J Mauro31,2Global Health Outcomes, Merck, Sharpe and Dohme Corporation, Whitehouse Station, NJ, USA; 3Clinical Research, Merck Research Laboratories, Upper Gwynedd, PA, USABackground: The purpose of this study was to identify a real-world US population having undergone surgery for malignant melanoma and describe treatment patterns, health care resource utilization, and costs for patients who subsequently received interferon alfa-2b (IFN) therapy or other standard of care chemotherapies.Methods: A retrospective cohort study was conducted using administrative claims from MarketScan® databases among melanoma patients diagnosed between 2004 and 2008 who had surgery and were subsequently treated with IFN or other chemotherapies. Health care resource utilization and costs of services (converted to 2009 dollars) were evaluated. Cost refers to the amount paid to providers associated with the health service.Results: Of 18,075 subjects with melanoma surgery claims, 1525 (8.4%) were treated with IFN and 1194 (6.6%) with other chemotherapies. Median duration (days) and number of doses of IFN therapy were 29 and 20, respectively. Approximately half of patients who received IFN discontinued therapy within or after the one-month induction phase. For IFN therapy patients, average total cost per patient for the last melanoma-related surgery prior to start of therapy, including costs of the surgery itself, pathology, anesthesia, and hospital care, was $2219. The average total cost per patient related to IFN therapy was $1188; this included costs for drug, office visits, blood work, and infusions. Other chemotherapy costs ranged from $146 to $2678.Conclusion: There is an unmet treatment need, considering that this study observed that melanoma patients on IFN therapy post-surgery do not complete the recommended one-year course of treatment which may compromise its full therapeutic benefits. Further study to investigate reasons for discontinuation may be warranted. In addition, costs associated with adjuvant IFN therapy in post-surgical treatment of disease are likely acceptable.Keywords: malignant melanoma, interferon alfa-2b, post-surgery, claims data, costs, resource utilization